Menganalisis Permasalahan Ketidaksesuaian Objek dalam Transaksi Jual Beli di Marketplace - Pulungan, Ja’far Hamzah; lubis, muhammad ridwan (BISMA : Business and Management Journal, 2023)
In this digital era, the marketplace has become a popular platform for sellers and buyers to transact online. However, there are still problems that arise related to the incompatibility of the object purchased with what is received by the buyer. This research will identify the factors that cause object discrepancies in buying and selling transactions in the marketplace andanalyze their impact on consumers and sellers. The research method used is secondary data analysis involving literature studies and reviews of Islamic law related to buying and selling transactions. The results of this research are expected to provide a better understanding of the problems related to object incompatibility in buying and selling transactions in the marketplaceand principles of Islamic law.